Ø§Ù„Ù…Ø³ØªÙˆÙŠØ§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ù„ØØ¯ÙŠØ«Ø© Ø¨ÙŠÙ† Ø§Ù„Ù…ØØ§ÙØ¸Ø© ÙˆØ§Ù„ØªØ·ÙˆÙ‘Ø± - Sayyid Megawer Sakran, Megawer (Jurnal CMES, 2018)
Arabic scholars from the classical to the modern period paid attention to the disciplines of Arabic lexicography. A great attention was given to lexicography, which was fundamentally helpful for active users and speakers of the Arabic language since the era of Khalil bin Ahmad (786 AD) who wrote the Al-â€˜Ain dictionary to Ahmad Mukhtar Umar's (2003) period with his dictionary MuÊ»jamu al-Lughah al-â€˜Arabiyyah al-MuÊ»Äshirah. Modern linguistic studies then produce language levels found in Arabic dictionaries. This level of language is certainly different in the view of Arab lexicographers. Some see it from the perspective of a language level that includes syntax, morphology and phonology, mostly referred to by classical and modern dictionaries. Some others see the language levels typically a variety of languages ammiyyah (al-â€˜ÄmmÄ«/colloquial Arabic) and various foreign languages (al-aÊ»jamÄ«/foreign language). Both of these varieties have seized the attention of Arabic dictionaries through a number of explanations either explicitly or implicitly in these dictionaries. Language levels additionally includes the treasure of language (turÄts) literary works are assessed as the basic foundation for language users and reviewers. In addition to turÄts, the level of spoken language used daily is also found in Arabic dictionaries. This language level undergoes articulation changes in a number of vocabularies in the form of changes at the vowel marks (charakat). This article outlines these four levels of language by modern Arabic dictionaries which aim to show the extent to which modern Arabic dictionaries make use of the classical Arabic lexicography paradigm and its contribution to the development of descriptions of language vocabulary for current language speakers and modern Arabic dictionary users.